β4GALT1 controls β1 integrin function to govern thrombopoiesis and hematopoietic stem cell homeostasis - Silvia Giannini (Nature Portfolio, 2020)
Mutations affecting sialylation and galactosylation affect megakaryocyte function and thrombopoiesis. Here the authors show that the enzyme β4GalT1 regulates thrombopoiesis and hematopoietic stem cell homeostasis by controlling beta-1 integrin function.